2023
DOI: 10.1177/0021955x231165343
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of density-dependent bead and cell structure of expanded polypropylene bead foams from X-ray computed tomography of different resolution

Abstract: Closed-cell bead foams with their hierarchical geometrical structure are a challenge for statistical reconstruction and finite element modelling. For the purpose of providing the fundamental micro- and meso-structural descriptors - wall thickness, cell as well as bead volume and sphericity - of expanded polypropylene bead foams of different density, 3D-images from X-ray computed tomography are analyzed. A detailed description of development and application of an image analysis methodology for the determination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…Cell wall bending and collapsing are considered to be the main drivers for the onset of nonlinear behavior. As these appear much earlier under compression than under tension and shear [8][9][10][11] different LVR limts are observed.…”
Section: Loading Direction-dependent Linear Viscoelastic Rangementioning
confidence: 99%
See 1 more Smart Citation
“…Cell wall bending and collapsing are considered to be the main drivers for the onset of nonlinear behavior. As these appear much earlier under compression than under tension and shear [8][9][10][11] different LVR limts are observed.…”
Section: Loading Direction-dependent Linear Viscoelastic Rangementioning
confidence: 99%
“…As the morphological properties like cell wall thickness and cell size as well as the described deformation mechanisms are randomly distributed, 4,9 the transitions between the three macroscopically observed stress-strain regions occur gradually. In addition, numerical simulations on closed-cell bead foams showed that the equivalent plastic strain on microscopic scale exceeds the macroscopically applied compressive strain by a factor of 10 easily.…”
Section: Introductionmentioning
confidence: 99%
“…8 Notably, foam extrusion facilitates cost-effective production of smaller bead batches, amalgamating solubilization, compounding, and expansion within a single-step process. 9,10 This approach also offers a narrower distribution of foamed bead sizes through controlled extrudate swell, 1114 coupled with facile density modification by adjusting blowing agent concentrations, 15 setting it apart from autoclave technology. 16 However, attaining precise process control and establishing a broad molding window remain formidable challenges, 1720 resulting in the limited prevalence of extrusion-produced ePE in the market.…”
Section: Introductionmentioning
confidence: 99%